Prognostic risk factors of early gastric cancer: a western experience - Haist, Thomas; Lorenz, Dietmar (Langenbeck's archives of surgery, 2016)
Lymph node metastasis (LNM) is the leading cause of tumor recurrence in early gastric cancer (EGC). Since endoscopic resection (ER) can be performed in EGC with curative intention when no LNM are present, this study wants to determine the risk factors for LNM in EGC.
Gesehen am 05.03.2020